Knockdown the P2X3 receptor in the stellate ganglia of rats relieved the diabetic cardiac autonomic neuropathy. (November 2018) - Sheng, Xuan; Dan, Yu; Dai, Bo; Guo, Jingjing; Ji, Huihong; Zhang, Xinge; Xie, Zhi; Song, Siqi; Pan, Qiwen; Wang, Jiayue; Liang, Shangdong; Li, Guilin
Abstract: Diabetic cardiac autonomic neuropathy (DCAN) is a common and serious complication of diabetes mellitus (DM), is manifested by nerve fiber injury in the sympathetic and parasympathetic nerve of the autonomic nervous system, and causes hypertension, cardiac arrhythmias, silent myocardial infarction, and sudden death. Our previous study observed that P2X3 receptor in superior cervical ganglia in rat was associated with sympathetic neuropathy caused by myocardial ischemia. However, whether the P2X3 receptor is involved in the diabetic cardiac autonomic neuropathy and the underlying mechanisms remain unclear. The aim of this research was explored the effect of P2X3 short hairpin RNA (shRNA) on information transmission of sympathetic nerve induced by DCAN. Sprague-Dawley (SD) male rats were randomly divided into four groups: Control, DM, DM treated with P2X3 shRNA and DM treated with scramble shRNA. Blood pressure, heart rate and heart rate variability were measured in each group. The expression of P2X3 in stellate ganglion (SG) was detected by immunohistochemistry, western blotting and QPCR. Results showed that P2X3 shRNA alleviated blood pressure and heart rate, improved heart rate variability, decreased the up-regulated expression levels of P2X3, interleukin-1beta and tumor necrosis factor alpha in stellate ganglion (SG) of diabetic rats. P2X3 shRNA also reduced the incremental concentration of serum epinephrine and the phosphorylation level of extracellular regulated protein kinases1/2 in diabetic rats. These results indicated that P2X3 shRNA could decrease sympathetic activity via inhibiting P2X3 receptor in the SG to alleviate DCAN. Highlights: Diabetes mellitus increased the sympathoexcitatory activity. P2X3 shRNA alleviated blood pressure and heart rate, improved heart rate variability. P2X3 shRNA decreased the elevated P2X3, IL-1β and TNF-α in SG of diabetic rats. P2X3 shRNA reduced the incremental concentration of serum epinephrine of DM rats. P2X3 shRNA reduced the phosphorylation level of ERK1/2 in the diabetic rats.